Does Social Media Usage Reduce the Level of Religiosity? - Juni Alfiah Chusjairi; Rini Sudarmanti (Jurnal the Messenger, 2024)
Introduction: This study examined the interplay between social media usage and religiosity among Indonesian Muslims, which is the largest Muslim country in the world. Morevoer where more than 70% of the population are active on social media. The social media platforms included in the study were networking sites such as facebook, to microblogging platforms such as Twitter and Instagram. Video sharing services such as YouTube were also examined.